Solid electrolyte, method for preparing same, and all-solid-state battery comprising same
By doping gallium cations into the sulfide-based solid electrolyte and controlling the composition ratio of lithium ions, an electrolyte with a sulfur-silver germanium ore-type crystal structure is formed, which solves the problem of reaction between the sulfide-based electrolyte and moisture, and achieves efficient moisture stability and ion conductivity.
Patent Information
- Application Number
- CN202480003795.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-01-30
- Filing Date
- 2024-01-30
- Publication Date
- 2025-03-28
AI Technical Summary
The sulfide-based solid electrolyte has strong reactivity with moisture, resulting in the formation of harmful gas hydrogen sulfide, affecting workers' safety and reducing electrolyte performance.
A solid electrolyte with a sulfur-silver germanium ore crystal structure is adopted to inhibit impurities generation and improve ion conductivity and moisture stability by doping gallium cations and controlling the composition ratio of lithium ions.
Excellent stability to moisture is achieved, decomposition and degradation of solid electrolyte particles is suppressed, high ion conductivity is maintained, and the safety and performance of the battery are improved.
Smart Images

Figure CN119731829A_ABST
Abstract
Description
Technical Field
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of Korean Patent Application No. 10-2023-0012072 filed on January 30, 2023 in the Korean Intellectual Property Office, the disclosure of which is incorporated herein by reference in its entirety. Technical Field
[0003] The present invention relates to a solid electrolyte having an argyrodite-type crystal structure with improved air stability, a preparation method thereof, and an all-solid-state battery comprising the same. Background Art
[0004] An all-solid-state battery is a battery that uses a solid electrolyte instead of the liquid electrolyte filled between the positive and negative electrodes of a conventional lithium secondary battery. It is safe because it has no risk of explosion, and its energy density is higher than that of a conventional battery, so it has attracted much attention as the next generation of batteries. The solid electrolyte used in an all-solid-state battery is a solid material that can conduct lithium ions in the battery and has a high ion conductivity similar to that of the electrolyte currently used in lithium secondary batteries. The core materials that make up the solid electrolyte include polymers, sulfides, oxides, etc., but among them, sulfide-based solid electrolytes with high ductility and high ion conductivity are evaluated as suitable for manufacturing large-scale batteries with high capacity.
[0005] However, sulfide-based solid electrolytes are highly reactive with moisture, and thus have the problem of reacting not only with moisture in the air but also with moisture under low humidity conditions to generate harmful gas hydrogen sulfide (H2S). Therefore, there is the problem of toxic hydrogen sulfide adversely affecting worker safety and also deteriorating the performance of the sulfide-based solid electrolyte itself.
[0006] Therefore, it is necessary to develop a sulfide-based solid electrolyte with excellent air stability.
[0007] (Patent Document 001) KR 10-2017-0021751 A Summary of the invention
[0008] Technical issues
[0009] An object of the present invention is to provide a solid electrolyte with improved air stability, in particular moisture stability.
[0010] However, the objects to be achieved by the present invention are not limited to the above objects, and other unmentioned objects may be apparent to those skilled in the art based on the following description.
[0011] Technical Solution
[0012] In order to achieve the above-mentioned object, the present invention provides a solid electrolyte, a preparation method thereof and an all-solid-state battery.
[0013] (1) The present invention provides a solid electrolyte having a composition represented by the following chemical formula 1:
[0014] [Chemical formula 1]
[0015] Li 11-(5a+3b+c+2x) P a Ga b S 5-(c+x) X 1+c
[0016] In the above chemical formula 1, X is one or more selected from F, Cl, Br and I, and
[0017] 5.0<5a+3b+c+2x<6.0, 0 <b≤0.5,0≤c<0.7,0<c+x<1,1≤a+b≤1.5。
[0018] (2) In the above (1), the present invention provides a solid electrolyte, wherein b is 0.01≤b≤0.3.
[0019] (3) In the above (1) or (2), the present invention provides a solid electrolyte, wherein 5a+3b+c+2x is 5.0<5a+3b+c+2x≤5.7.
[0020] (4) In any one of the above (1) to (3), the present invention provides a solid electrolyte, wherein the solid electrolyte has an argyrodite type crystal structure.
[0021] (5) In any one of the above (1) to (4), the present invention provides a solid electrolyte, wherein the ion conductivity retention rate of the solid electrolyte according to the following Mathematical Formula 1 is 60% or more.
[0022] [Mathematical formula 1]
[0023] Ion conductivity retention rate (%) = Ion conductivity after exposure to moisture (mS / cm) / Initial ion conductivity (mS / cm) × 100
[0024] In the above Mathematical Formula 1, the initial ion conductivity is a value measured at 22° C. immediately after the solid electrolyte is prepared, and
[0025] The ionic conductivity after exposure to moisture is a value measured at 22° C. immediately after the solid electrolyte was exposed to air at a relative humidity of 1.91% for 5 hours.
[0026] (6) In the above (5), the present invention provides a solid electrolyte wherein the initial ion conductivity is 2.0 mS / cm or more and 20.0 mS / cm or less.
[0027] (7) In the above (5) or (6), the present invention provides a solid electrolyte, wherein the ion conductivity after exposure to moisture is 1.2 mS / cm or more and 12.0 mS / cm or less.
[0028] (8) In any one of the above (1) to (7), the present invention provides a solid electrolyte, wherein the total impurity content of the solid electrolyte is 2% by weight or less.
[0029] (9) The present invention provides a method for preparing a solid electrolyte, the method comprising:
[0030] S1: dry-mixing a sulfide-based solid electrolyte raw material and a doping element to prepare a precursor mixture, and
[0031] S2: thermally treating the precursor mixture,
[0032] The sulfide-based solid electrolyte raw materials include Li2S, P2S5 and LiX,
[0033] X is F, Cl, Br or I, and
[0034] The content of Li2S is greater than 0.97 mol and less than 2.5 mol relative to 1 mol of LiX, and
[0035] The doping element is Ga.
[0036] (10) In the above (9), the present invention provides a method for preparing a solid electrolyte, wherein step S1 is performed by ball milling the sulfide-based solid electrolyte raw material and the doping element.
[0037] (11) In the above (9) or (10), the present invention provides a method for preparing a solid electrolyte, wherein the heat treatment in step S2 is performed at a temperature of 300°C to 600°C.
[0038] (12) The present invention provides an all-solid-state battery, comprising the solid electrolyte according to any one of (1) to (8) above.
[0039] Beneficial Effects
[0040] The solid electrolyte according to the present invention is doped with Ga and controls the composition ratio of lithium ions to be below a desired level, and thus, it is possible to suppress impurity generation and improve ion conductivity and moisture stability.
[0041] Furthermore, the solid electrolyte according to the present invention has a low content of unreacted or side-reacted impurities and has a uniform composition, and thus can have the effects of excellent ion conductivity and air stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 XRD data for impurity detection used to evaluate Example 1 and Comparative Example 2 are shown. DETAILED DESCRIPTION
[0043] The present invention will be described in more detail below to facilitate understanding of the present invention.
[0044] It should be understood that the words or terms used in this document should not be interpreted as having the meanings defined in commonly used dictionaries. It should also be understood that based on the principle that the inventor can appropriately define the meanings of words or terms in order to explain the invention in the best way, the words or terms should be interpreted as having the meanings consistent with their meanings in the context of the relevant technology and the technical concept of the present invention.
[0045] The terms used herein are only used to describe exemplary embodiments and are not intended to limit the present invention. Terms in the singular may include plural forms unless the context clearly indicates otherwise.
[0046] In the present specification, it should be understood that the terms "include", "comprises" or "has" are intended to specify the presence of stated features, numbers, steps, elements or a combination thereof, but do not exclude the presence or addition of one or more other features, numbers, steps, elements or a combination thereof.
[0047] The term "all-solid-state battery" used in this specification refers to a battery in which all components of the battery are solid, which is distinguished from a liquid electrolyte secondary battery using a liquid electrolyte such as an electrolyte and a gel polymer secondary battery using a polymer electrolyte instead of a separator and also using a liquid electrolyte.
[0048] Solid electrolyte
[0049] The solid electrolyte according to the present invention has a composition represented by the following Chemical Formula 1. In this case, the solid electrolyte has high ion conductivity, low reactivity with a lithium negative electrode, and can suppress decomposition and degradation of solid electrolyte particles when the solid electrolyte is exposed to moisture or oxygen.
[0050] [Chemical formula 1]
[0051] Li11-(5a+3b+c+2x) P a Ga b S 5-(c+x) X 1+c
[0052] In the above chemical formula 1, X is one or more selected from F, Cl, Br, and I, and 5 < 5a + 3b + c + 2x < 6, 0 < b ≤ 0.5, 0 ≤ c < 0.7, 0 < c + x < 1, 1 ≤ a + b ≤ 1.5.
[0053] On the other hand, in the case of Li6PS5Cl, Li6PS5Br, etc. used as solid electrolytes having a thiogallate-type crystal structure in the art, there are the following problems: S contained in the solid electrolyte 2- ions react with moisture in the air and are easily decomposed. However, the solid electrolyte having a thiogallate-type crystal structure according to the present invention can improve air stability by doping gallium (Ga) cations having excellent binding force with sulfur (S) ions, suppress impurity generation by controlling the composition ratio of lithium (Li) ions to a predetermined level or less, and has the effects of excellent ionic conductivity and air stability.
[0054] According to one embodiment of the present invention, b can be 0 < b ≤ 0.5, and 5a + 3b + c + 2x can be 5.0 < 5a + 3b + c + 2x < 6.0. Specifically, b can be 0.01 or more, 0.05 or more, 0.07 or more, 0.09 or more, 0.5 or less, 0.48 or less, 0.44 or less, 0.4 or less, 0.36 or less, 0.34 or less, 0.3 or less, 0.26 or less, 0.22 or less, 0.20 or less, 0.16 or less, 0.14 or less, 0.12 or less, or 0.10 or less. In addition, 5a + 3b + c + 2x can be greater than 5.1, greater than 5.2, greater than 5.3, greater than 5.4, greater than 5.5, less than 6.0, less than 5.9, less than 5.8, less than 5.7, and less than 5.6. If the above numerical ranges are satisfied, the doping amount of Ga cations is appropriate, thereby suppressing degradation or deterioration when the solid electrolyte particles are exposed to moisture or oxygen. However, when synthesizing a solid electrolyte doped with Ga cations, impurities such as Li2S or LiBr may be generated, thereby reducing the ionic conductivity. In this case, by reducing the composition ratio of lithium element, the solid electrolyte can exist in a thiogallate phase with a low impurity content or no impurities, and thus, the ionic conductivity can be improved.
[0055] In addition, a may be from 0.5 to less than 1.5, and x may be from greater than 0 to less than 1. Specifically, a may be greater than 0.5, greater than 0.6, greater than 0.7, greater than 0.8, greater than 0.9, greater than 0.95, less than 1.5, less than 1.4, less than 1.3, less than 1.2, less than 1.1, or less than 1.0, and x may be greater than 0, greater than 0.1, greater than 0.2, greater than 0.3, greater than 0.4, greater than 0.5, less than 1.0, less than 0.9, less than 0.8, less than 0.7, or less than 0.6. If the above numerical range is met, the sulfide solid electrolyte can improve lithium ion conductivity.
[0056] According to one embodiment of the present invention, in terms of high ion conductivity and low reactivity with the lithium negative electrode, the sulfide-based solid electrolyte of the present invention may also have a argyrodite-type crystal structure. When the sulfide-based solid electrolyte has an argyrodite-type crystal structure, this means that the sulfide-based solid electrolyte has at least a crystalline phase of an argyrodite-type structure as the main phase. At this time, the main phase refers to the phase with the largest proportion relative to the total amount of all crystalline phases constituting the sulfide solid electrolyte. Therefore, relative to all crystalline phases constituting the sulfide-based solid electrolyte, the content ratio of the crystalline phase of the argyrodite-type structure contained in the sulfide-based solid electrolyte is preferably 80% by mass or more, more preferably 85% by mass or more, 90% by mass or more, or 95% by mass or more.
[0057] According to one embodiment of the present invention, the ion conductivity retention rate of the solid electrolyte according to the following mathematical formula 1 may be 60% or more, specifically 65% or more, 70% or more, 75% or more, 80% or more, 85% or more or 90% or more.
[0058] [Mathematical formula 1]
[0059] Ion conductivity retention rate (%) = Ion conductivity after exposure to moisture (mS / cm) / Initial ion conductivity (mS / cm) × 100
[0060] In the above Mathematical Formula 1, the initial ionic conductivity is a value measured at 22° C. and a relative humidity of 0.7% immediately after the solid electrolyte is prepared, and the ionic conductivity after exposure to moisture is a value measured at 22° C. immediately after the solid electrolyte is exposed to air with a relative humidity of 1.91% for 5 hours.
[0061] According to one embodiment of the present invention, the initial ion conductivity of the solid electrolyte is 2.0 mS / cm or more and 20.0 mS / cm or less. Specifically, the initial ion conductivity may be 3.0 mS / cm or more, 4.0 mS / cm or more, 5.0 mS / cm or more, 6.0 mS / cm or more, 20.0 mS / cm or less, 19.0 mS / cm or less, or 18.0 mS / cm or less. The higher the initial ion conductivity of the electrolyte, the better, but if the initial ion conductivity satisfies the above range, the effect of improving process stability and moisture stability may be excellent.
[0062] According to the present invention, the ionic conductivity of the solid electrolyte after exposure to moisture can be from 1.2 mS / cm to 12.0 mS / cm. Specifically, the ionic conductivity can be 1.4 mS / cm or more, 1.5 mS / cm or more, 1.6 mS / cm or more, 1.7 mS / cm or more, 12.0 mS / cm or less, or 11.0 mS / cm or less. In this case, as in the case of the initial ionic conductivity, the higher the ionic conductivity of the electrolyte after exposure to moisture, the better, but if the ionic conductivity after exposure to moisture satisfies the above range, thereby satisfying the numerical range of the ionic conductivity retention rate according to the above mathematical formula 1, there is the following advantage: during the battery manufacturing process, despite exposure to moisture, the degradation rate of the ionic conductivity is reduced and the electrolyte structure remains unchanged.
[0063] According to one embodiment of the present invention, the total impurity content of the solid electrolyte may be less than 2 wt %. The impurities may be included in non-reactants that are not reacted during the preparation of the solid electrolyte, or side reactions produced by side reactions, and specifically, the impurities may be Li2S or LiA. Here, A in the above impurities may be one or more elements selected from F, Cl, Br and I. In addition, the content of the impurities may be obtained by analyzing the XRD data of the solid electrolyte powder using the Rietveld refinement program.
[0064] The total content of the impurities can be less than 2 wt %. The content of impurities is based on 100 wt % of the solid electrolyte. For example, the content of the impurities can be less than 2.0 wt %, less than 1.9 wt %, less than 1.8 wt %, less than 1.7 wt %, less than 1.6 wt %, less than 1.5 wt %, less than 1.4 wt %, less than 1.3 wt %, less than 1.2 wt %, less than 1.1 wt %, less than 1.0 wt %, less than 0.9 wt %, less than 0.8 wt %, less than 0.7 wt %, less than 0.6 wt %, less than 0.5 wt %, less than 0.4 wt %, less than 0.3 wt %, less than 0.2 wt % or less than 0.1 wt %. If the content of the impurities meets the above range, it can be confirmed that the precursor has been micronized and prepared by uniform mixing, and a solid electrolyte with a desired uniform composition can be obtained. In addition, the solid electrolyte prepared by uniform mixing can have high ionic conductivity and low electronic conductivity, and can have an excellent ionic conductivity retention level by suppressing decomposition or degradation of the solid electrolyte particles when exposed to moisture or oxygen, thereby obtaining excellent performance characteristics when the solid electrolyte is applied to an all-solid-state battery.
[0065] Method for preparing solid electrolyte
[0066] The method for preparing a solid electrolyte of the present invention comprises:
[0067] S1: dry-mixing a sulfide-based solid electrolyte raw material and a doping element to prepare a precursor mixture, and
[0068] S2: heat-treating the precursor mixture.
[0069] In addition, the sulfide-based solid electrolyte raw material may include Li2S, P2S5 and LiX, wherein the X may be F, Cl, Br or I, the content of the Li2S may be greater than 0.97 mol to less than 2.5 mol relative to 1 mol of LiX, and the doping element may be Ga.
[0070] The solid electrolyte prepared by the method for preparing a solid electrolyte of the present invention may have the technical characteristics of the above-mentioned solid electrolyte, and the same contents as those described with respect to the solid electrolyte will be omitted.
[0071] According to one embodiment of the present invention, the content of Li2S may be greater than 0.97 mol to less than 2.5 mol, specifically greater than 0.97 mol to less than 2.5 mol, less than 2.4 mol or less than 2.3 mol, relative to 1 mol of LiX. If the solid electrolyte is prepared by satisfying the above numerical range, the composition ratio of the lithium element can be controlled, thereby suppressing the generation of impurities and improving the ion conductivity.
[0072] According to one embodiment of the present invention, the step S1 can be performed by ball milling the sulfide-based solid electrolyte raw material and the doping element. Specifically, the step S1 can be performed by ball milling the sulfide-based solid electrolyte raw material and the doping element using a planetary mill containing zirconium oxide (Zr) balls.
[0073] According to one embodiment of the present invention, step S1 can be performed as follows: a sulfur (Li2S) precursor, a phosphorus (P2S5) precursor and a LiX precursor as raw materials for a sulfide-based solid electrolyte are introduced into a zirconia container, and ZrO2 balls are added thereto, followed by stirring and ball milling. In addition, the precursor mixture prepared in step S1 can be in powder form.
[0074] If a solid electrolyte is prepared by wet mixing such as slurrying or solubilization, part of the solvent will remain in the precursor mixture or the solid electrolyte in a carbonized state even if a drying or heat treatment process is performed, thereby causing a problem of increased electronic conductivity. Therefore, according to the method for preparing a solid electrolyte of the present invention, the precursor of the sulfide-based solid electrolyte in powder form is dry-mixed to induce uniform mixing, and the ion conductivity of the prepared solid electrolyte can be maximized.
[0075] On the other hand, in the process of ball milling using a planetary mill, the higher the stirring speed, the faster the generation rate of the solid electrolyte precursor mixture, the smaller the particle size, the longer the stirring time, and the higher the conversion rate to the uniformly mixed solid electrolyte precursor mixture. The stirring time can be more than 3 hours, more than 6 hours, more than 8 hours, more than 10 hours, more than 12 hours, more than 14 hours or more than 24 hours, and the stirring speed can be more than 300 rpm, more than 400 rpm, more than 500 rpm, more than 600 rpm, more than 700 rpm or more than 800 rpm.
[0076] According to one embodiment of the present invention, the heat treatment of step S2 can be performed at a temperature of 300°C to 600°C. More specifically, the heat treatment temperature can be above 300°C, above 350°C, above 400°C, above 450°C, above 500°C, below 600°C or below 550°C. If the heat treatment temperature is within the above range, a argyrodite phase can be formed from the precursor mixture. In particular, if high-energy grinding of more than 600 rpm is performed in step S1, the amorphous powder-type precursor mixture can be crystallized into an argyrodite solid electrolyte through the heat treatment process. In addition, if the above-mentioned heat treatment temperature range is met, the problem of residual unreacted precursors can be solved, and the problem of increased electronic conductivity due to sulfur loss can also be solved.
[0077] All-solid-state battery
[0078] The present invention provides an all-solid-state battery comprising the above solid electrolyte.
[0079] Specifically, the all-solid-state battery comprises: a positive electrode containing a positive electrode active material, a negative electrode containing a negative electrode active material, and a solid electrolyte layer containing the solid electrolyte according to the present invention disposed between the positive electrode and the negative electrode.
[0080] The all-solid-state battery according to the present invention has a small decrease in ionic conductivity due to moisture, and thus the initial efficiency, life characteristics, and output characteristics of the battery can be excellent.
[0081] At this time, the all-solid-state battery of the present invention can be manufactured by a method generally known in the art. For example, the all-solid-state battery can be manufactured by laminating and pressing so that a solid electrolyte layer exists between the positive electrode and the negative electrode.
[0082] (1) Positive electrode
[0083] The positive electrode can be manufactured by coating a positive electrode paste containing a positive electrode active material, a binder, a conductive material, a solvent, etc. on a positive electrode current collector.
[0084] There is no particular limitation on the positive electrode current collector as long as it has conductivity and does not cause chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. can be used. In addition, fine irregularities can be formed on the surface of the positive electrode current collector to improve the binding force of the positive electrode active material, and the positive electrode current collector can be used in various forms such as a film, a sheet, a foil, a net, a porous body, a foam body, and a non-woven fabric body.
[0085] The positive electrode active material is a compound capable of reversibly inserting and extracting lithium. Specifically, it can contain a lithium metal oxide containing one or more metals such as cobalt, manganese, nickel, and aluminum and lithium. More specifically, the lithium metal oxide can be a lithium manganese-based oxide (such as LiMnO2, LiMn2O4, etc.), a lithium cobalt-based oxide (such as LiCoO2, etc.), a lithium nickel-based oxide (such as LiNiO2, etc.), a lithium nickel manganese-based oxide (such as LiNi 1-Y Mn Y O2 (where 0 < Y < 1), LiMn 2-z Ni z O4 (where 0 < Z < 2), etc.), a lithium nickel cobalt-based oxide (such as LiNi 1-Y1 Co Y1 O2 (where 0 < Y1 < 1), etc.), a lithium manganese cobalt-based oxide (such as LiCo 1-Y2Mn Y2 O2 (where 0 <Y2<1)、LiMn 2-z1 Co z1 O4 (where 0<Z1<2, etc.), lithium nickel manganese cobalt oxides (such as Li(Ni p Co q Mn r1 )O2 (where 0<p<1, 0<q<1, 0<r1<1, and p+q+r1=1) or Li(Ni p1 Co q1 Mn r2 )O4 (where 0<p1<2, 0<q1<2, 0<r2<2, and p1+q1+r2=2) etc.) or lithium nickel cobalt transition metal (M) oxide (e.g. Li(Ni p2 Co q2 Mn r3 A S2 )O2 (wherein M is selected from Al, Fe, V, Cr, Ti, Ta, Mg and Mo, and p2, q2, r3 and s2 are each the atomic fractions of a single element, wherein 0<p2<1, 0<q2<1, 0<r3<1, 0<s2<1, and p2+q2+r3+s2=1), etc.), etc., and may contain any one of them or a mixture of two or more thereof.
[0086] Among them, since the capacity performance and stability of the battery can be increased, the lithium metal oxide can be LiCoO2, LiMnO2, LiNiO2, lithium nickel manganese cobalt oxide (such as Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 )O2、Li(Ni 0.6 Mn 0.2 Co 0.2 )O2、Li(Ni 0.5 Mn 0.3 Co 0.2 )O2、Li(Ni 0.7 Mn 0.15 Co 0.15 )O2、Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, etc.) or lithium nickel cobalt aluminum oxide (e.g. Li(Ni 0.8 Co 0.15 Al 0.05 )O2, etc.). When considering the significant improvement effect brought about by the type and content ratio control of the constituent elements forming the lithium metal oxide, the lithium metal oxide may be Li(Ni 0.6 Mn 0.2 Co 0.2 )O2、Li(Ni0.5 Mn 0.3 Co 0.2 )O2、Li(Ni 0.7 Mn 0.15 Co 0.15 )O2、Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, etc., and any one of them or a mixture of two or more thereof can be used.
[0087] The positive electrode active material may be contained in an amount of 60 to 99 wt %, preferably 70 to 99 wt %, and more preferably 80 to 98 wt %, relative to the total weight of solids excluding the solvent in the positive electrode slurry.
[0088] The binder is a component used to assist the bonding between the conductive material, the active material and the current collector. Examples of the binder may include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber, sulfonated ethylene propylene diene monomer rubber, styrene-butadiene rubber, fluororubber, various copolymers thereof, and the like.
[0089] Generally, the binder may be contained in an amount of 1 to 20 wt %, preferably 1 to 15 wt %, and more preferably 1 to 10 wt %, relative to the total weight of solids excluding the solvent in the positive electrode slurry.
[0090] The conductive material is a component for further improving the conductivity of the positive electrode active material.
[0091] There is no particular limitation on the conductive material as long as it has conductivity without causing chemical changes in the battery. For example, graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; fluorocarbons; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives, etc. can be used.
[0092] Generally, the content of the conductive material may be 1 wt % to 20 wt %, preferably 1 wt % to 15 wt %, and more preferably 1 wt % to 10 wt %, relative to the total weight of solids excluding the solvent in the positive electrode slurry.
[0093] The solvent may include an organic solvent such as N-methyl-2-pyrrolidone (NMP), and its amount may be such that a preferred viscosity is achieved when the positive electrode active material is included and optionally a binder, a conductive material, etc. For example, the content of the solvent may be such that the concentration of the solid containing the positive electrode active material and optionally the binder and the conductive material is 50 wt % to 95 wt %, preferably 70 wt % to 95 wt %, and more preferably 70 wt % to 90 wt %.
[0094] (2) Negative electrode
[0095] The negative electrode may be manufactured by, for example, coating a negative electrode slurry containing a negative electrode active material, a binder, a conductive material, a solvent, etc. on a negative electrode collector, or a graphite electrode made of carbon (C) or metal itself may be used as the negative electrode.
[0096] For example, when the negative electrode is manufactured by coating the negative electrode slurry on the negative electrode collector, the thickness of the negative electrode collector is generally 3 to 500 μm. There is no particular limitation on the negative electrode collector as long as it has high conductivity and does not cause chemical changes in the battery, for example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, as in the case of the positive electrode collector, fine concavoconvexities can be formed on the surface of the negative electrode collector to improve the binding force of the negative electrode active material, and the negative electrode collector can be used in various forms, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.
[0097] Examples of the negative electrode active material may include one or more negative electrode active materials selected from the following: natural graphite, artificial graphite, carbonaceous materials; metal-containing substances such as lithium-containing titanium composite oxide (LTO), Si, SiO x , Sn, Li, Zn, Mg, Cd, Ce, Ni or Fe; alloys composed of metal (Me); oxides of metal (Me) (MeO x ); and a composite material of metal (Me) and carbon. Specifically, as the negative electrode active material, a material containing silicon (Si), silicon oxide (SiO x ), silicon-based negative electrode active materials such as silicon alloys. In this case, a thin and stable SEI layer containing siloxane bonds can be formed, thereby further improving the high temperature stability and life characteristics of the battery.
[0098] The negative electrode active material may be contained in an amount of 60 to 99 wt %, preferably 70 to 99 wt %, and more preferably 80 to 98 wt %, relative to the total weight of solids excluding the solvent in the negative electrode slurry.
[0099] The binder is a component used to assist the bonding between the conductive material, the active material and the current collector. Examples of the binder may include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber, sulfonated ethylene propylene diene monomer rubber, styrene-butadiene rubber, fluororubber, various copolymers thereof, and the like.
[0100] Generally, the binder may be contained in an amount of 1 to 20 wt %, preferably 1 to 15 wt %, and more preferably 1 to 10 wt %, relative to the total weight of solids excluding the solvent in the negative electrode slurry.
[0101] The conductive material is a component for further improving the conductivity of the negative electrode active material. There is no particular limitation on the conductive material as long as it has conductivity without causing chemical changes in the battery. For example, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; fluorocarbons; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive materials such as polyphenylene derivatives, etc. can be used.
[0102] The conductive material may be contained in an amount of 1 to 20 wt %, preferably 1 to 15 wt %, and more preferably 1 to 10 wt %, relative to the total weight of solids excluding the solvent in the negative electrode slurry.
[0103] The solvent may include water, or an organic solvent such as N-methyl-2-pyrrolidone (NMP), and its amount may be such that a preferred viscosity is achieved when the negative electrode active material is included and optionally a binder, a conductive material, etc. For example, the content of the solvent may be such that the concentration of the solid containing the negative electrode active material and optionally the binder and the conductive material is 50 wt % to 95 wt %, preferably 70 wt % to 90 wt %.
[0104] When the metal itself is used as the negative electrode, the metal film itself can be used as the negative electrode, or the negative electrode can be manufactured by physically bonding, rolling or depositing the metal on the negative electrode current collector. The deposition method can be electrical phase deposition or chemical vapor deposition.
[0105] For example, the metal film itself or the metal bonded / rolled / deposited on the negative electrode current collector can be a metal selected from lithium (Li), nickel (Ni), tin (Sn), copper (Cu) and indium (In), or an alloy of two metals thereof.
[0106] (3) Solid electrolyte layer
[0107] The solid electrolyte layer may further include a binder in addition to the solid electrolyte according to the present invention.
[0108] The binder is a component used to assist the bonding between the conductive material, the active material and the current collector. Examples of the binder may include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber, sulfonated ethylene propylene diene monomer rubber, styrene-butadiene rubber, fluororubber, various copolymers thereof, and the like.
[0109] Generally, the content of the binder may be 1 wt % to 20 wt %, preferably 1 wt % to 15 wt %, and more preferably 1 wt % to 10 wt %, relative to the total weight of the solid electrolyte layer.
[0110] The present invention provides a battery module including an all-solid-state battery as a unit cell and a battery pack including the battery module. The battery module and the battery pack include secondary batteries having high capacity, high rate characteristics and cycle characteristics, and can therefore be used as power sources for medium and large devices selected from electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.
[0111] The preferred embodiments of the present invention will be described in detail below to help understand the present invention. However, the embodiments are only for illustration of the present invention, and therefore, it is obvious to those skilled in the art that various modifications and variations can be made without departing from the scope and spirit of the present invention as disclosed in the appended claims. It is obvious that these variations and modifications fall within the scope of the appended claims.
[0112] Examples and Comparative Examples
[0113] Example 1
[0114] Four precursors, namely Li2S, P2S5, LiBr and Ga2S3, were dry mixed (ball milled) at a molar ratio of 2.25:0.45:1:0.05. During dry mixing, a planetary ball milling device with zirconia balls was used, which rotated at a rate of 300 rpm to 700 rpm for uniform mixing. Then, the obtained mixed precursor was crystallized by heat treatment at 450°C to 550°C for 12 hours, and then pulverized by ball milling to obtain a solid electrolyte with a argyrodite-type crystal structure, whose composition is Li 5.5 P 0.9 Ga 0.1 S 4.65 Br1.0 All the above processes were carried out in an inert Ar atmosphere.
[0115] The above-mentioned Li having an argyrodite-type crystal structure is used 5.5 P 0.9 Ga 0.1 S 4.65 Br 1.0 As the solid electrolyte of Example 1.
[0116] Example 2
[0117] Four precursors, namely Li2S, P2S5, LiBr and Ga2S3, were dry mixed (ball milled) at a molar ratio of 2.25:0.475:1:0.025. During dry mixing, a planetary ball milling device with zirconia balls was used, which rotated at a rate of 300 rpm to 700 rpm for uniform mixing. Then, the obtained mixed precursor was crystallized by heat treatment at 450°C to 550°C for 12 hours, and then pulverized by ball milling to obtain a solid electrolyte with a argyrodite-type crystal structure, whose composition is Li 5.5 P 0.95 Ga 0.05 S 4.7 Br 1.0 All the above processes were carried out in an inert Ar atmosphere.
[0118] The above-mentioned Li having an argyrodite-type crystal structure is used 5.5 P 0.95 Ga 0.05 S 4.7 Br 1.0 As the solid electrolyte of Example 2.
[0119] Comparative Example 1
[0120] The three precursors, namely Li2S, P2S5 and LiBr, were dry mixed (ball milled) at a molar ratio of 2.5:0.5:1. During the dry mixing, a planetary ball milling device with zirconia balls was used, which rotated at a rate of 300 rpm to 700 rpm for uniform mixing. Then, the obtained mixed precursor was crystallized by heat treatment at 450°C to 550°C for 12 hours, and then pulverized by ball milling to prepare Li6PS5Br having a argyrodite-type crystal structure. 1.0 All the above processes were carried out in an inert Ar atmosphere.
[0121] The above-mentioned Li6PS5Br with argyrodite crystal structure is used 1.0 As the solid electrolyte of Comparative Example 1.
[0122] Comparative Example 2
[0123] Four precursors, namely Li2S, P2S5, LiBr and Ga2S3, were dry mixed (ball milled) at a molar ratio of 2.6:0.45:1:0.05. During dry mixing, a planetary ball milling device with zirconia balls was used, which rotated at a rate of 300 rpm to 700 rpm for uniform mixing. Then, the obtained mixed precursor was crystallized by heat treatment at 450°C to 550°C for 12 hours, and then pulverized by ball milling to prepare Li2S having an Argentite-type crystal structure. 6.2 P 0.9 Ga 0.1 S5B 1.0 All the above processes were carried out in an inert Ar atmosphere.
[0124] The above-mentioned Li having an argyrodite-type crystal structure is used 6.2 P 0.9 Ga 0.1 S5B 1.0 As the solid electrolyte of Comparative Example 2.
[0125] Comparative Example 3
[0126] Four precursors, namely Li2S, P2S5, LiCl and LiBr, were dry mixed (ball milled) at a molar ratio of 1.9:0.5:1.2:0.4. During dry mixing, a planetary ball milling device with zirconia balls was used, which rotated at a rate of 300 rpm to 700 rpm for uniform mixing. Then, the obtained mixed precursor was crystallized by heat treatment at 450°C to 550°C for 12 hours, and then pulverized by ball milling to prepare Li2S having an Argentite-type crystal structure. 5.4 PS 4.4 Cl 1.2 Br 0.4 All the above processes were carried out in an inert Ar atmosphere.
[0127] The above-mentioned Li having an argyrodite-type crystal structure is used 5.4 PS 4.4 Cl 1.2 Br 0.4 As the solid electrolyte of Comparative Example 3.
[0128] Comparative Example 4
[0129] The three precursors, namely Li2S, P2S5 and LiCl, were dry mixed (ball milled) at a molar ratio of 1.9:0.5:1.6. During the dry mixing, a planetary ball milling device with zirconia balls was used, which rotated at a rate of 300 rpm to 700 rpm for uniform mixing. Then, the obtained mixed precursor was crystallized by heat treatment at 450°C to 550°C for 12 hours, and then pulverized by ball milling to prepare Li2S having an Argentite-type crystal structure. 5.4 PS 4.4 Cl 1.6 All the above processes were carried out in an inert Ar atmosphere.
[0130] The above-mentioned Li having an argyrodite-type crystal structure is used 5.4 PS 4.4 Cl 1.6 As the solid electrolyte of Comparative Example 4.
[0131] Comparative Example 5
[0132] Four precursors, namely Li2S, P2S5, LiCl and LiBr, were dry mixed (ball milled) at a molar ratio of 1.9:0.5:1.0:0.6. During dry mixing, a planetary ball milling device with zirconia balls was used, which rotated at a rate of 300 rpm to 700 rpm for uniform mixing. Then, the obtained mixed precursor was crystallized by heat treatment at 450°C to 550°C for 12 hours, and then pulverized by ball milling to prepare Li2S having an Argentite-type crystal structure. 5.4 PS 4.4 Cl 1.0 Br 0.6 All the above processes were carried out in an inert Ar atmosphere.
[0133] The above-mentioned Li having an argyrodite-type crystal structure is used 5.4 PS 4.4 Cl 1.0 Br 0.6 As the solid electrolyte of Comparative Example 5.
[0134] Comparative Example 6
[0135] The three precursors, namely Li2S, P2S5 and LiBr, were dry mixed (ball milled) at a molar ratio of 2.2:0.5:1.0. During the dry mixing, a planetary ball milling device with zirconia balls was used, which rotated at a rate of 300 rpm to 700 rpm for uniform mixing. Then, the obtained mixed precursor was crystallized by heat treatment at 450°C to 550°C for 12 hours, and then pulverized by ball milling to prepare Li2S having an Argentite-type crystal structure. 5.4 PS 4.7 Br1.0 All the above processes were carried out in an inert Ar atmosphere.
[0136] The above-mentioned Li having an argyrodite-type crystal structure is used 5.4 PS 4.7 Br 1.0 As the solid electrolyte of Comparative Example 6.
[0137] Comparative Example 7
[0138] The three precursors, namely Li2S, P2S5 and LiBr, were dry mixed (ball milled) at a molar ratio of 2.15:0.5:1.0. During the dry mixing, a planetary ball milling device with zirconia balls was used, which rotated at a rate of 300 rpm to 700 rpm for uniform mixing. Then, the obtained mixed precursor was crystallized by heat treatment at 450°C to 550°C for 12 hours, and then pulverized by ball milling to prepare Li2S having an Argentite-type crystal structure. 5.3 PS 4.65 Br 1.0 All the above processes were carried out in an inert Ar atmosphere.
[0139] The above-mentioned Li having an argyrodite-type crystal structure is used 5.3 PS 4.65 Br 1.0 As the solid electrolyte of Comparative Example 7.
[0140] Experimental Example 1: Evaluation of ion conductivity retention
[0141] - Measurement of initial ionic conductivity
[0142] Immediately after preparation, 150 mg of each solid electrolyte powder prepared in Examples 1 and 2 and Comparative Examples 1 to 7 was taken and introduced into a SUS mold with a diameter of 13 mm. The mold was mounted on a press together with PEEK for insulation, and a constant potentiostat was connected to the SUS mold. After pressing at 370 MPa to make the electrolyte structure dense enough, the pressure was slowly reduced and maintained at 100 MPa, and the AC impedance was measured from a measurement frequency of 1 Hz to 7 MHz. Using the Nyquist plot, the ionic conductivity was calculated based on the measured resistance value, as shown in Table 1 below. All measurements were carried out in a dry room at a temperature of 22°C and a relative humidity of 0.7%.
[0143] - Measurement of ionic conductivity after exposure to moisture
[0144] After exposure to air at a relative humidity of 1.91% for 5 hours, 150 mg of each solid electrolyte powder prepared in Examples 1 and 2 and Comparative Examples 1 to 7 was taken and introduced into a SUS mold with a diameter of 13 mm. The mold was mounted on a press together with PEEK for insulation, and a constant potentiostat was connected to the SUS mold. After pressing at 370 MPa to make the electrolyte structure dense enough, the pressure was slowly reduced and maintained at 100 MPa, and the AC impedance was measured from a measurement frequency of 1 Hz to 7 Mhz. Using the Nyquist plot, the ionic conductivity after exposure to moisture was calculated based on the measured resistance value, as shown in Table 1 below. All measurements were carried out in a dry room at a temperature of 22°C and a relative humidity of 0.7%.
[0145] The ion conductivity retention rate was calculated according to the following mathematical formula 1, as shown in Table 1.
[0146] [Mathematical formula 1]
[0147] Ion conductivity retention rate (%) = Ion conductivity after exposure to moisture (mS / cm) / Initial ion conductivity (mS / cm) × 100
[0148]
[0149] Examples 1 and 2 are cases where gallium cations are doped and the molar number of lithium (11-(5a+3b+c+2x)) is controlled to be less than 6, wherein the solid electrolytes of each of Examples 1 and 2 are confirmed to have an ion conductivity retention rate greater than 60%. Therefore, the solid electrolyte of the present invention has the effect of reducing the degradation rate of ion conductivity after exposure to moisture and maintaining the electrolyte structure even when exposed to moisture.
[0150] On the other hand, Comparative Examples 1 to 7 are cases where gallium cations are not doped or the molar number of lithium is 6 or more, in which the ion conductivity retention rate is lower than that of the solid electrolytes of Examples 1 and 2. In particular, in the case of Comparative Example 2, although gallium cations are doped, the molar number of lithium corresponds to 6 or more, so it can be confirmed that the ion conductivity retention rate is low. In addition, in the case of Comparative Examples 3 to 7, after exposure to moisture, the ion conductivity is significantly reduced, corresponding to a low level of ion conductivity, so exposure to moisture may cause problems in the electrolyte structure and manufacturing process stability.
[0151] Experimental Example 2: Evaluation of Impurity Detection
[0152] Evaluation of impurity detection of Example 1 and Comparative Example 2. Impurity detection of solid electrolyte powder was calculated using XRD measurement and Rietveld refinement analysis. For the XRD equipment, Bruker's D8 Endeavor, Cu Kα radiation, and a wavelength of 1.5406 Å were used, and measurement conditions with a scanning rate of 2° / min and a 2θ angle of 10° to 90° were applied under non-atmospheric exposure. Impurities were identified using the TOPAS Rietevld refinement program, and impurity detection was evaluated. The XRD data of Example 1 and Comparative Example 2 are shown in FIG. Figure 1 And as shown in Table 2.
[0153]
[0154] Refer to Table 2 and Figure 1 In the case of Example 1 in which gallium is doped but the molar number of lithium is less than 6, no impurities are detected, but in the case of Comparative Example 2 in which the molar number of lithium is greater than 6, impurities such as Li2S or LiBr are generated, so the ion conductivity may be reduced. Therefore, it can be confirmed that the ion conductivity retention rate is also poor.
Claims
1. A solid electrolyte having a composition represented by the following chemical formula 1: [Chemical formula 1] Li 11-(5a+3b+c+2x) P a Ga b S 5-(c+x) X 1+c Wherein in the above chemical formula 1, X is one or more selected from F, Cl, Br and I, and 5.0<5a+3b+c+2x<6.0, 0 <b≤0.5,0≤c<0.7,0<c+x<1,1≤a+b≤1.5。 2 . The solid electrolyte according to claim 1 , wherein b is 0.01≤b≤0.
3.
3. The solid electrolyte according to claim 1, wherein the 5a+3b+c+2x is 5.0<5a+3b+c+2x≤5.
7. 4 . The solid electrolyte according to claim 1 , wherein the solid electrolyte has an argyrodite type crystal structure.
5. The solid electrolyte according to claim 1, wherein the ion conductivity retention rate of the solid electrolyte according to the following mathematical formula 1 is 60% or more: [Mathematical formula 1] Ion conductivity retention rate (%) = Ion conductivity after exposure to moisture (mS / cm) / Initial ion conductivity (mS / cm) × 100 In the above mathematical formula 1, The initial ionic conductivity is a value measured at 22° C. immediately after the solid electrolyte is prepared, and The ionic conductivity after exposure to moisture is a value measured at 22° C. immediately after the solid electrolyte was exposed to air at a relative humidity of 1.91% for 5 hours. 6 . The solid electrolyte according to claim 5 , wherein the initial ion conductivity is 2.0 mS / cm or more and 20.0 mS / cm or less. 7 . The solid electrolyte according to claim 5 , wherein the ion conductivity after exposure to moisture is 1.2 mS / cm or more and 12.0 mS / cm or less. 8 . The solid electrolyte according to claim 1 , wherein the total impurity content of the solid electrolyte is 2 wt % or less.
9. A method for preparing a solid electrolyte, the method comprising: (S1) dry-mixing a sulfide-based solid electrolyte raw material and a doping element to prepare a precursor mixture; as well as (S2) heat treating the precursor mixture, in: The sulfide-based solid electrolyte raw material comprises Li2S, P2S5 and LiX; X is F, Cl, Br or I; The content of Li2S is greater than 0.97 mol and less than 2.5 mol relative to 1 mol of LiX; and The doping element is Ga. 10 . The method according to claim 9 , wherein the step (S1) is performed by ball milling the sulfide-based solid electrolyte raw material and the doping element.
11. The method according to claim 9, wherein the heat treatment in the step (S2) is performed at a temperature of 300°C to 600°C. 12 . An all-solid-state battery, comprising the solid electrolyte according to claim 1 .
Citation Information
Patent Citations
Electrode active material-solid electrolyte composite, method for manufacturing the same, and all solid state rechargeable lithium battery including the same
KR1020170021751A
MIC antibodies and binding agents and methods of use thereof
KR1020230012072A